Interleukin-37 inhibits inflammation activation and disease severity of PM2.5-induced airway hyperresponsiveness - Min Wang (Elsevier, 2021)
We have shown in the past studies that fine particulate matter (PM2.5) exposure increases airway hyperresponsiveness and leads to lung inflammation damage. Interleukin (IL)-37 plays a inhibitory role in inflammation activation and maintenance. However, the function of IL-37 in the above processes keep unclear. We aim to explore the role of IL-37 in PM2.5-induced airway hyperresponsiveness in this study. A nose-only PM2.5 online concentration, enrichment and exposure instrument was also applied to generate mice model of airway hyperresponsiveness. A transgenic mice strain using a CMV promoter to express human IL-37b (hIL-37tg) was obtained. PM2.5 exposure was shown to increase airway resistance, followed by lung inflammation and IL-1β, TNFα, and IL-6 release, which was inhibited by IL-37tg mice and mice administrated recombinant human IL-37 intranasally (i.n). Moreover, expression of the proliferation-related protein PCNA and migration-related proteins MMP-2, MMP-9, and Vimentin was reduced in lung tissues of IL-37tg mice and mice given recombinant human IL-37 i.n. Abnormal cell contraction, proliferation, and migration of human airway smooth muscle cells (hASMCs) incubated with PM2.5 were also decreased by IL-37 treatment. In addition, IL-37 intervention of hASMCs before PM2.5 incubation decreased cytoplasmic calcium level and expression of PCNA, MMP-2, MMP-9 and Vimentin. Finally, knockdown of the IL-37 receptor IL-1R8 gene eliminated the protective effects of IL-37 in the above responses. We conclude that IL-37 inhibits inflammation activation and disease severity of airway hyperreactivity by PM2.5 induction.